APPLICATION OF INFORMATION TECHNOLOGY IN THE GREEN ECONOMY - Tashpulatov Javoxir Avaz ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The rapid advancement of information technology (IT) has catalyzed the transition toward a green economy, fostering sustainable practices across industries. This article explores the integration of IT in promoting environmental sustainability, emphasizing its role in resource management, energy efficiency, and reducing carbon footprints. Through a comprehensive analysis of literature, methods, and case studies, the study highlights the impact of IT on the green economy and suggests further directions for research and application.